Kajian Literatur: Penanganan Psikologis Pada Remaja Dengan Bullying Menggunakan Cognitive Behaviour Therapy - Wulan, Winda Ratna (Yayasan Healing and Healthcare Education, 2025)
Bullying is a form of violent behavior characterized by psychological or physical coercion against an individual or a group of individuals who are perceived as